REPRODUCTIVE AND SPATIAL CHARACTERISTICS OF MAY BEETLES’ POPULATIONS (SCARABAEIDAE, MELOLONTHINAE) IMPORTANT FOR THE OPTIMIZATION OF COMMON PINE PROTECTION - Korenchuk, E. V.; Drozda, V. F.; Fokin, A. V. (Scientific Progress & Innovations, 2020)
In recent years, there has been an increase in populations of May beetles. This is closely related to the risks of functioning nursery gardens and young pine crops. In order to optimize protection technology, it is necessary to have a clear understanding of the peculiarities of the phytophages’ bio-ecology (Melolontha melolontha L., Melolontha hippocastani F., Polyphylla fullo L., Anoxia pilosa F., Amphimallon volgensis Fisch.), in particular as to the formation of the reproductive potential of May beetle females, the dynamics of their oviposition, egg viability, layer localization of eggs, larvae and diapause pupae in soils. That is why their research was the purpose of the work. The study was conducted under typical conditions of the central Forest–Steppe. To determine the forage value of leaves of woody crops, females were placed in screen gar- dens with leaves of common oak, white poplar, drooping birch, apple trees, inflorescences of common pine. Determining the depth of eggs, larvae and pupae location was performed in layers: digging out at 0–10, 11–20, 21–30, 31–40, 41–50, 51–60, 61–75, 76–90, 91, 91–130, 131–150 cm in areas of 0.25 m2. There were 50 calculation points. It has been established that oak leaves is the optimal substrate as to female fertility, and the females, which were fed with pine inflorescences are also characterized by significant reproductive potential. The dynamics of oviposition has been established. The first period lasts 5–7 days. During this pe- riod females lay from 17.8 to 29.4 % of eggs. Physiologically complete eggs of the female are laid in the pe- riod of mass oviposition, which lasts 12–14 days. During the third oviposition period of 4–7 days, females lay a significant number of physiologically defective eggs. Larvae born from eggs laid during the period of mass oviposition are the greatest threat to plantings. Depending on the depth of location, the greatest viabil- ity is shown by eggs laid in a layer up to 30 cm; in general, in the surface layers of 10 cm) and 31–40 cm eggs are most vulnerable to the influence of abiotic and biotic regulators. The distribution of larvae in the soil shows that in May the depth of 10–30 cm is the most technological for applying bio-preparations– up to 75 % of larvae are concentrated in this layer; in June – July the most appropriate application depth is up to 20 cm; at the beginning of August, it is advisable to apply preparations at a depth of 20–40 cm – the concen- tration of larvae is up to 88 % here; at the end of August and throughout September larvae are found in lay- ers up to 30 cm – 60–88 %, at the end of September and in October–November the main number of larvae, up to 85 %, focuses at the wintering depth of 50–75 cm, i.e. the introduction of preparations at this depth is technologically unjustified. It has been shown that only 11.8 % of pupae population is concentrated at a depth of up to 7 cm. Their death rate for the period of spring reactivation is 65.2%. The following soil layers of 8–15, 16–24, and 25–35 cm contained 80.6 % of pupae. Their death rate was 14.3–15.4 %. In general, the viable part of May beetle populations is 84.6–85.7 %, which is a real threat to plantings.